Observações sobre geometria sintética - Bassan, André Roberto [UNESP] (2015)
The objective of this work is to present some results of Euclidean geometry which are given in elementary and high school from the synthetic point of view, that is we will not assume the metric axioms. As an application we will make some constructions using the developed tools